Association between overactive bladder and suicidal ideation in US adults: a population-based study - Liu, Heng; Dong, Huqiang; Jin, Mingchu; Zhou, Yu; Hao, Haidong; Yuan, Yutang; Jia, Hongtao; Li, Junyong (Frontiers in Psychiatry, 2025)
BackgroundSuicidal ideation, a critical public health issue, is notably associated with mental health disorders. Overactive bladder (OAB), a prevalent urological disorder, significantly impacts patients’ quality of life and is associated with mental health problems such as anxiety and depression. This study investigates the association between OAB and suicidal ideation in US adults.MethodsThis population-based cross-sectional study utilized data from six consecutive NHANES datasets (2007-2018). Suicidal ideation was assessed using the ninth item of the Patient Health Questionnaire-9 (PHQ-9), and OAB was identified through a simplified Overactive Bladder Symptom Score (OABSS). Multivariate logistic regression models, Restricted Cubic Splines, and subgroup analyses were used to analyze. The association between OAB and suicidal ideation, adjusting for potential confounders.ResultsAmong the 28,085 participants, 3.30% reported suicidal ideation, and 20.39% were identified with OAB. Individuals with suicidal ideation had a significantly higher prevalence of OAB compared to those without suicidal ideation. After adjusting for covariates, each point increase in OABSS was associated with a 15% higher likelihood of suicidal ideation (OR=1.15, 95% CI: 1.10-1.20). Participants with OAB had a 47% increased likelihood of suicidal ideation compared to those without OAB (OR=1.47, 95% CI: 1.26-1.72). Subgroup analysis proved the robustness of the results of this study.ConclusionThe findings indicate a significant positive association between OAB and suicidal ideation in US adults. These findings underscore the necessity of integrating urological and mental health care to enhance suicide prevention strategies.